Principles of Neurophysiological Assessment, Mapping, and Monitoring - Kaye, Alan David; Davis, Scott Francis (Springer eBooks, 2014)
This book provides foundational knowledge of intraoperative monitoring (IOM) and is written for the range of clinicians who monitor the function of the nervous system during surgery, from new technologists to neurophysiologists and neurosurgeons.  Early chapters describe the building blocks of IOM in accessible terms and are followed by practical chapters on monitoring and mapping that show basic and clinical science "in action".  Anesthesiologists and trainees with an interest in diagnosing and managing pain will appreciate the inclusion of chapters on the electrophysiological assessment of spinal cord pathology and on the treatment of pain.   Principles of Neurophysiological Assessment, Mapping, and Monitoring is designed for use as a text in academic courses or in corporate training programs.  It also provides a concise refresher for experienced clinicians and for physicians, neurophysiologists, and technologists preparing for board exams.